Speculative indigeneities: the [k]new now - Bhagat, Heeten (Department of Drama, 2020)
The starting point of this research study began with a broad and unwieldly question - what would Zimbabwe look like if colonisation didn’t happen? This question arose with regard to the launch of the Indigenisation and Economic Empowerment Act (IEEA) in 2007 and is focused of on building an understanding of notions of indigeneity in Zimbabwe through an inquiry of indigenousness and indigenisation. The methodological approach is designed as an interdisciplinary and experimental research inquiry that processes these debates and proposes an expansion of the probabilities of notions of indigeneity within the range of existing socio-political, economic and historical analyses of indigenousness and indigenisation in Zimbabwe. This exploration begins with a broad historical, anthropological and etymological survey of the term 'indigenous’ that is interwoven with a contextual account of Zimbabwe and its socio-political lifespan. The primary site of investigation is the independence-day ceremony that took place at the National Sports Stadium in Harare, Zimbabwe on the 18th of April 2017. This focus is motivated by two distinctive elements at this event - a banner that declares 'ZIMBABWE WILL NEVER BE A COLONY AGAIN’ and a fragment from the president’s speech that asserts, 'we can now call ourselves full masters of our destiny’ (Mugabe 2017). This event stands as a crucial node for the debates and questions this research aims to pose regarding notions of indigenisation, indigenousness and registers of indigeneity. Political and socio-economic analyses of this annual ritual tower above the lacuna of analysis of its performance logics. This performance-specific inquiry aims to contribute new meanings and complexity around the event. The information generated from this reading is further processed through the mechanisms of speculative research as a way to think beyond the dilemmas and paradoxes that emerge from the historical, anthropological and performance analyses of this event. The penultimate chapter of this dissertation suggests a conceptual rehearsal of the findings generated through an expanded understanding of queer theory. The final articulation of 2 this research investigation extends the experimental approach, presenting a set of visual, aural and sculptural elements as the conclusion. The dissertation offers alternate readings of notions of homogeneity and singularity. It is also constituted as a way to understand the probability of building new knowledges through lateral and rhizomic processes as a journey that gathers and synthesizes from across a number of disciplines. The contention of this thesis, then, is to suggest an expansion of the notion of indigeneity towards the possibility of polygeneity, a notion that aims to align with the conceptual constructs of cosmopolitanism (Appiah 2006, Kleingeld and Brown 2014), which engage arguments for expanded understandings of contemporary identity formation. Embodied in this suggestion of polygeneity lies the potential to revive notions of dynamism and creativity that have been dormant since the onset of European colonisation in Zimbabwe. In the wake of the 'new dawn’ in Zimbabwe, in this moment of growing debates for alternatives, the thesis finds its impulse in the imperative for radical and creative shifts in consciousness to activate new ideas, new readings, and new knowledges.